Asp-376-Glu substitution endows target-site resistance to AHAS inhibitors in Limnocharis flava, an invasive weed in tropical rice fields - Zakaria, Norazua; Ruzmi, Rabiatuladawiyah; Moosa, Salmah; Asib, Norhayu; Zulperi, Dzarifah; Ismail, Siti Izera; Ahmad Hamdani, Muhammad Saiful (Springer, 2021)
Limnocharis flava (L.) Buchenau is a problematic weed in rice fields and water canals of Southeast Asia, and in Malaysia this invasive aquatic weed species has evolved multiple resistance to synthetic auxin herbicide and acetohydroxyacid synthase (AHAS) inhibitors. In this study, it was revealed that, a single nucleotide polymorphism (SNP) at amino acid position 376, where C was substituted to G at the third base of the same codon (GAC to GAG), resulting in Aspartate (Asp) substitution by Glutamate (Glu) was the contributing resistance mechanism in the L. flava population to AHAS inhibitors. In vitro assay further proved that, all the L. flava individuals carrying AHAS resistance mutation exhibited decreased-sensitivity to AHAS inhibitors at the enzyme level. In the bensulfuron-methyl whole-plant bioassay, high resistance indices (RI) of 328- and 437-fold were recorded in the absence and presence of malathion (the P450 inhibitor), respectively. Similarly, translocation and absorption of bensulfuron-methyl in both resistant and susceptible L. flava populations showed no remarkable differences, hence eliminated the possible co-existence of non-target-site resistance mechanism in the resistant L. flava. This study has confirmed another new case of a target-site resistant weed species to AHAS-inhibitors.